Self-assembly of bis-salphen compounds: from semiflexible chains to webs of nanorings. Issue 7 (19th January 2018) - Pyrlin, Sergey V.; Hine, Nicholas D. M.; Kleij, Arjan W.; Ramos, Marta M. D.
Abstract : A mechanism is proposed explaining self-assembly of webs of interconnected microrings of bis-salphen compounds based on molecular level simulations of their structure and aggregation in solvent. Abstract : The recently-observed self-assembly of certain salphen-based compounds into neuron-like networks of microrings interconnected with nano-thin strings may suggest a new highly-potent tool for nanoscale patterning. However, the mechanism behind such phenomena needs to be clarified before they can be applied in materials design. Here we show that, in contrast with what was initially presumed, the emergence of a "rings-and-rods" pattern is unlikely to be explained by merging, collapse and piercing of vesicles as in previously reported cases of nanorings self-assembly via non-bonding interactions. We propose an alternative explanation: the compounds under study form a 1D coordination polymer, the fibres of which are elastic enough to fold into toroidal globules upon solvent evaporation, while being able to link separate chains into extended networks. This becomes possible because the structure of the compound's scaffold is found to adopt a very different conformation from that inferred in the original work. Based on ab initio and molecular dynamics calculations we propose a step-by-step description of self-assembly process of a supramolecular structure which explains all the observed phenomena in a simple and clear way. The individual roles of the compound' s scaffold structure, coordination centres, functional groups and solvent effects are also explained, opening a route to control the morphology of self-assembled networks and to synthesize new compounds exhibiting similar behaviour.